Desarrollo del pensamiento crítico a través del debate crítico: una mirada cualitativa (2021)
The training of students in the development of critical and analytical skills constitutes one of the main challenges of education nowadays. In this context, critical debate favors the interconnection of opposing positions through reflection, inquiry, defense, and reasoned judgment processes. For this reason, it is necessary to recognize how the critical debate strategy contributes to the development of critical thinking in university students. To this end, an action research was carried out, framed in an intervention program with psychology students, which included explanation sessions, execution of critical debates, and mentoring. The data collection techniques used were participant observation, field diary, record of mentoring sessions, and evaluation. The information analysis was carried out through the recollection, organization, categorization, and triangulation of information with the reference framework. The intervention program allowed the development of critical thinking skills such as interpretation, analysis, evaluation, inference, explanation, and discernment, as well as auxiliary skills including self confidence, active listening, teamwork, knowledge management, and applicability of what is learned into everyday life. Critical debate is a strategy that contributes to the development of own and complementary critical thinking skills, showing the relevance of its implementation and application in educational practice.